In harm's way : a history of Christian peacemaker teams - Kern, Kathleen, 1962- ([Place of publication not identified] : Casemate Publishers and Book Distributors, LLC, 2014)
In 1984, Evangelicals for Social Action founder Ron Sider posed the question: ""What would happen if we in the Christian church developed a new non-violent peacekeeping force ready to move into violent conflicts and stand peacefully between warring parties. . . Everyone assumes that for the sake of peace it is moral and just for soldiers to get killed by the hundreds of thousands, even millions. Do we not have as much courage and faith as soldiers?"" Christian Peacemaker Teams (CPT) has been trying to answer those questions since 1986. CPT has responded to invitations from grassroots organiser.
14. Twenty Years and CountingBibliography; About CPT; Back cover.
Vendor-supplied metadata.
Keywords: Christian Peacemaker Teams; Christian Peacemaker Teams; Peace -- Religious aspects -- Mennonites; War -- Religious aspects -- Mennonites; Nonviolence -- Religious aspects -- Christianity; Christian Peacemaker Teams; Nonviolence -- Religious aspects -- Christianity; Peace -- Religious aspects -- Mennonites; War -- Religious aspects -- Mennonites; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Nonviolence -- Religious aspects -- Christianity; Peace -- Religious aspects -- Mennonites; War -- Religious aspects -- Mennonites; Electronic books